Сorrespondence analysis as a tool for computer modeling of sustainable development - Berezka, Kateryna; Kovalchuk, Olha (Analiza korespondencji jako narzędzie do modelowania komputerowego zrównoważonego rozwoju, 2018)
Many of the problems that the world faces today appeared as the result of unstable development. Global climate change, resource depletion, space debris, poverty, inequality, and threats to global security are the main but not the only challenges for modern humanity. The important issue in studying the problems of sustainable development of the countries in the world is the development of strategies that would give an opportunity to avoid environmental and social catastrophes. The correspondence analysis is used to identify the relationship between the Happy Planet Index (which is an aggregate indicator of achievements in the key aspects of human development, such as life duration and quality, distribution uniformity, access to knowledge, and preservation of environment) and Gross National Income (one of the basic metrics of the population welfare level). The analysis led to the conclusion that the income level of the population is not the main factor in assessing the level of sustainable development of a country. The obtained results can give important and useful information for social institutions and politicians
Econometrics = Ekonometria, 2018, Vol. 22, No. 4, s. 9-23
Keywords: sustainability development; correspondence analysis; computer modeling; Happy PlanetIndex; Gross National Income